First solve the quadratic using the quadratic formula

`x = (-B +- sqrt(B^2 - 4AC))/(2A)`

where `A = 2a`, `B = a-3` and `C = a -1`

This gives solutions

`x = (3-a +- sqrt((a-3)^2 - 4(2a)(a-1)))/(4a)`

` = (3-a +- sqrt(a^2 - 6a + 9 - 8a^2 + 8a))/(4a)`

`=...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

First solve the quadratic using the quadratic formula

`x = (-B +- sqrt(B^2 - 4AC))/(2A)`

where `A = 2a`, `B = a-3` and `C = a -1`

This gives solutions

`x = (3-a +- sqrt((a-3)^2 - 4(2a)(a-1)))/(4a)`

` = (3-a +- sqrt(a^2 - 6a + 9 - 8a^2 + 8a))/(4a)`

`= (3-a +- sqrt(-7a^2 + 2a + 9))/(4a)`

Now, the determinant `-7a^2 + 2a + 9` factorizes to `(9-7a)(a+1)`

and because `-7a + 2a + 9` is concave then it is positive between it's two roots

`a = -1` and `a = 9/7`

When the determinant is positive, there are at least two real roots, so

the equation has real solutions when `a: a in [-1,9/7]` **answer**